The Indonesian Defense Management Concept In Resolving The Israel-Palestine Conflict - Ibnu Asakir; Hikmat Zakky Almubaroq (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The Israel-Palestine conflict is a complex international issue that affects global geopolitical dynamics and security. The Indonesian government has taken strategic steps in defense management through international forums to support a peaceful solution to the conflict. This study aims to analyze how Indonesia applies the concept of defense management in responding to the Israel-Palestine conflict. A qualitative research method with a descriptive-analytical approach was used, with primary and secondary data collected through interviews, observations, and verifications. The results show that Indonesia focuses on diplomacy, international cooperation, and advocacy for a fair resolution of the conflict. Through active participation in international forums such as the United Nations and the Organization of Islamic Cooperation, Indonesia demonstrates its commitment to supporting the rights of the Palestinian people and encouraging the resolution of the conflict through dialogue and negotiation. Challenges faced include global political dynamics, the interests of major countries, and differences in views among members of international forums. This study provides insights into Indonesia's role in contributing to world peace and maintaining geopolitical stability.